Therapeutic Potential and Mechanistic Insights of Sunflower Receptacles’ Essential Oil Against Gout: An In-Depth Molecular Study (Communications in Computational Chemistry, 2025)
Gout is a common chronic disease caused by the deposition of monosodium urate crystals. Previousstudies confirmed the anti-gout effects of sunflower receptacles. For example, eupatoriochromene may beone of the most important compounds for reducing uric acid and relieving gout, which can be extractedfrom the essential oil of sunflower receptacles (EOSR). However, the other active components in EOSRand their anti-gout molecular mechanisms remain unclear. In this work, we employed widespreadmethods such as network pharmacology, machine learning algorithm, molecular docking, and moleculardynamics simulation, to investigate the anti-gout molecular mechanisms of the EOSR components. Theprotein-protein interaction (PPI) network confirmed that the components of EOSR exert anti-gouteffects mainly by targeting inflammatory targets. GO and KEGG enrichment analyses revealed thatthe components of EOSR play roles in several important biological pathways, potentially providing anti-gout effects through various mechanisms. Additionally, since the target URAT1 plays a critical role inthe treatment of gout, we investigated the interactions between two components of EOSR, Linoleic acid(La) and Kauren-19-oic acid (Koa), and target URAT1 using machine learning algorithm, moleculardocking and molecular dynamics simulation. It confirmed that La and Koa can stably bind to URAT1and shift its conformation to the Inward-facing state. Similar to the positive control Benzbromarone(Ben), both La and Koa induce secondary structural changes in URAT1, with Koa sharing key residueswith Ben. This research further indicates the molecular mechanisms of EOSR in treating gout andexpands the range of therapeutic agents for it.